2012
DOI: 10.1074/jbc.m112.406413
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Inhibits the Proliferation of Neural Progenitor Cells and Hippocampal Neurogenesis

Abstract: Background: Resveratrol has been suggested to have protective effects against many diseases, but its biological actions on brain in healthy subjects are unclear. Results: Resveratrol impaired hippocampal neurogenesis and memory acquisition by AMPK activation and suppression of pCREB and BDNF. Conclusion: Resveratrol impairs hippocampal neurogenesis and cognitive function. Significance: Unlike DR and exercise, resveratrol can adversely affect neurogenesis and cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 69 publications
2
54
1
Order By: Relevance
“…In our preliminary experiment, we observed that 50 and 100 μmol/L resveratrol decreased NSC viability. Park and Leong reported that resveratrol at high concentrations (20 and 50 μmol/L, 30-120 μmol/L, respectively) inhibited proliferation of NPCs and embryonic cardiomyoblasts [26,27]. Therefore, further studies should investigate whether resveratrol exhibits a dual concentration effect for neurogenesis in different physiological or pathological states.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our preliminary experiment, we observed that 50 and 100 μmol/L resveratrol decreased NSC viability. Park and Leong reported that resveratrol at high concentrations (20 and 50 μmol/L, 30-120 μmol/L, respectively) inhibited proliferation of NPCs and embryonic cardiomyoblasts [26,27]. Therefore, further studies should investigate whether resveratrol exhibits a dual concentration effect for neurogenesis in different physiological or pathological states.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al reported that resveratrol inhibited hippocampal neurogenesis of healthy mice (1-10 mg/kg body weight), and proliferation of NPCs in culture (20 and 50 μmol/L) [26]. Leong et al reported that 30-120 μmol/L resveratrol inhibited the proliferation of embryonic cardiomyoblasts [27].…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemicals and Adaptive Responses et al, 2013). On the other hand, resveratrol can downregulate CREB activity and BDNF production in the hippocampus of unstressed mice (Park et al, 2012a). This suggests that resveratrol might differentially regulate BDNF expression depending upon the level of stress encountered by neurons.…”
Section: B Trophic Signaling Pathwaysmentioning
confidence: 99%
“…Park and Leong et al reported that 20 and 50 μmol/L, 30-120 μmol/L, respectively, resveratrol inhibited proliferation of neural progenitor cells and embryonic cardiomyoblasts [45,46]. Sugino's study showed that 10 and 20 μmol/L resveratrol strengthened nerve growth factor-induced neurite outgrowth in PC12 cells [47].Ren and Tang et al reported that 5 μmol/L resveratrol increased proliferation of neural stem cells and promoted synaptogenesis and neurite outgrowth of neurons after OGD/R injury [20,21].…”
Section: Discussionmentioning
confidence: 99%